Three-dimensional Hansen Solubility Parameters as Predictors of Miscibility in Cocrystal Formation - Payghan, Dr. Santosh Ambadas (Asian Journal of Pharmaceutics (AJP), 2017)
The objective of this study was to investigate whether the miscibility of a drug and coformer, as predicted by Hansen solubility parameters (HSPs), can indicate cocrystal formulation. It was also our aim to evaluate various HSPs-based approaches in miscibility predication. It is concerned with some new aspects of solvent properties, and these properties can help predict solvent behavior during the manufacturing processes and will be useful in predicting behavior in many other fields of endeavor. The work on the solubility parameter, in particular, deals with fundamental attractions among materials and should have broad application. To say that hydrogen bonding had no significant effect on solvent retention without defining hydrogen bonding was not satisfactory. To better define hydrogen bonding and polar bonding, a study based on the solubility parameter was initiated. This eventually led to the concept of a three-dimensional (3D) solubility parameter (E). The 3D solubility parameter is has been assumed that ΔE is given by the simple sum of the energies arising from dispersion forces, ΔEd, polar forces, ΔEP, and hydrogen bonding forces, ΔEh. Group contribution method for the estimation of Hansen solubility parameters of pure organic compounds is presented by characteristic groups ensure the prediction of HSP for a broad series of organic compounds, including those having complex multiring, heterocyclic, and aromatic structures. The predictions are exclusively based on the molecular structure of compounds, and no experimental data are needed. Solubility parameters for solutes are obtained by group contribution method. Using Fedor’s substituent constants, Hoy’s molar attraction constants and Van Kreevalen constants were calculated and are currently used methods. The resultant Δ values of active pharmaceutical ingredient and coformers are compared, and their solid-state miscibility is expressed. Possibility of cocrystal formulation by Krevlens is Δδ < 5MP and Greenhalgh Δδ < 7MP can be predicted.